Current advance methods for the identification of blast resistance genes in rice - Tanweer, Fatah A.; Rafii, Mohd Y.; Sijam, Kamaruzaman; A. Rahim, Harun; Ahmed, Fahim; Latif, Mohammad A. (Elsevier, 2015)
Rice blast caused by Magnaporthe oryzae is one of the most devastating diseases of rice around the world and crop losses due to blast are considerably high. Many blast resistant rice varieties have been developed by classical plant breeding and adopted by farmers in various rice-growing countries. However, the variability in the pathogenicity of the blast fungus according to environment made blast disease a major concern for farmers, which remains a threat to the rice industry. With the utilization of molecular techniques, plant breeders have improved rice production systems and minimized yield losses. In this article, we have summarized the current advanced molecular techniques used for controlling blast disease. With the advent of new technologies like marker-assisted selection, molecular mapping, map-based cloning, marker-assisted backcrossing and allele mining, breeders have identified more than 100 Pi loci and 350 QTL in rice genome responsible for blast disease. These Pi genes and QTLs can be introgressed into a blast-susceptible cultivar through marker-assisted backcross breeding. These molecular techniques provide timesaving, environment friendly and labour-cost-saving ways to control blast disease. The knowledge of host–plant interactions in the frame of blast disease will lead to develop resistant varieties in the future.